A Controlled Trial of Dissemination and Implementation of a Cardiovascular Risk Reduction Strategy in Small Primary Care Practices. (20th August 2020) - Cykert, S.; Keyserling, T.; DeWalt, D.; Pignone, M.; Cene, C.; Trogdon, J.
Abstract : Research Objective: Cardiovascular disease (CVD) remains the leading cause of death in the United States and is particularly devastating in the southeastern United States. Despite evidence‐based approaches that can reduce CVD risk, adoption of effective therapies remains slow. TheAUTHOR: Please check the usage of the phrase 'derived, population management dashboard' throughout the article. Heart Health Now (HHN) study was designed to evaluate the effect of combining practice facilitation with an electronic health record derived, population management dashboard based on atherosclerotic cardiovascular disease (ASCVD) 10‐year risk scores on reducing risk for patients at high baseline risk. Study Design: HHN was a step‐wedged, stratified, cluster‐randomized trial. Small primary care practices with 10 or fewer clinicians were enrolled. Practices were stratified by readiness and randomized to 6 cohorts according to start date. The 12‐month intervention began for Cohort 1 in January of 2016. The five subsequent cohorts started their intervention period every other month thereafter. The intervention consisted of onsite practice facilitation and a practice population dashboard stratified by ASCVD risk. Treatments to reduce risk included statin prescribing, blood pressure reduction, smoking cessation counseling, and aspirin use for high‐risk patients of appropriate age. Population Studied: ASCVD risk scores were assessed on 437 556 patients in 219 small NC primary care practices. We report on 146 826 patients with a > = 10% baseline risk of experiencing a stroke, heart attack, or death within 10 years. Principal Findings: Demographic characteristics of the high‐risk group included 66% of white race, 24% black, 3% Hispanic ethnicity, 54% male, and 52% residing in rural areas. The mean ASCVD 10‐year risk at baseline was 23.6% (SD ± 12.8%). After the intervention, the unadjusted mean score fell to 17.1% (SD ± 11.5%). After applying the stepped wedge and calendar time controls to the analysis, most (75%) of the 6.5% absolute risk reduction was attributable to the intervention. All demographic subgroups improved by at least 6% (range: 6.03%‐6.76%). In multivariate analysis, male gender, age > 65 years, low income (<$40 000), and black race ( P  <   0.001 for all variables) were each associated with greater [relative] risk reductions. Conclusions: A one‐year intervention utilizing practice facilitation and an electronic health record derived, population management dashboard for small primary care practices resulted in significant risk reductions for patients at high risk for cardiovascular disease or death. Implications for Policy or Practice: Implementation of practice facilitation and population management informatics support in small primary care practices can strongly drive the clinical use of new evidence and, in this case, dramatically reduce ASCVD risk. Primary Funding Source: The study was funded by Agency for Healthcare Research and Quality.